2016
DOI: 10.1186/s41121-016-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Reactionary and reparative dentin formation after pulp capping: Hydrogel vs. Dycal

Abstract: Background: After indirect capping, injured odontoblasts generate reactionary dentin, whereas after direct capping of a pulp exposure pulp, cells stimulate the formation of reparative dentin. The aim of this study was to evaluate and compare the effects of two direct capping agents on pulp tissue reactions: Hydrogel (a bovine serum albumin (BSA)/glutaraldehyde,) and Dycal (a calcium hydroxide-based capping agent). Methods: In 6-week-old male Sprague-Dawley rats, occlusal cavities were drilled in the first maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
(26 reference statements)
0
9
1
Order By: Relevance
“…A Njeh studied the reactionary and reparative dentin formation after pulp capping with Dycal ® . The thickness of reparative dentin varied between 100 and 200 μm (0.1-0.2 mm) after 4 weeks [28]. Whereas, in the present study the reparative dentin thickness formed by eggshell derived calcium hydroxyapatite (0.091 ± 0.003) was much higher than Dycal ® (0.061 ± 0.001) at the end of 3-months review.…”
Section: Discussioncontrasting
confidence: 71%
“…A Njeh studied the reactionary and reparative dentin formation after pulp capping with Dycal ® . The thickness of reparative dentin varied between 100 and 200 μm (0.1-0.2 mm) after 4 weeks [28]. Whereas, in the present study the reparative dentin thickness formed by eggshell derived calcium hydroxyapatite (0.091 ± 0.003) was much higher than Dycal ® (0.061 ± 0.001) at the end of 3-months review.…”
Section: Discussioncontrasting
confidence: 71%
“…Pulpal floors were further deepened until the unexposed pulp was seen through dentin as a pink spot. The pulp was then exposed in the middle of the pulpal floor using a sterile dental explorer (Hu-Friedy, USA) (Njeh et al, 2016). Bleeding was controlled by placement of a cotton pellet moistened with sterile saline until physiologic hemostasis occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it can be observed that CHX incorporation has not adversely affected the alkalinity of CHX-loaded/Ca(OH) 2 microparticles as the high pH values were maintained throughout ( Figure 6 a), as indicated in earlier studies [ 18 ]. When performing pulp capping, such high alkalinity of Ca(OH) 2 is known to incite an irritation potential, capable of inducing coagulation necrosis at the contact surface of the pulp [ 68 ]. Accordingly, the high pH values of the CHX-loaded/Ca(OH) 2 microparticles (at 15 days) indicate their promising potential for reparative dentin barrier formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, experiments involving a vital pulp and corresponding histological evaluation of the dentin-bridge formation will provide fertile ground for future research. Previous literature findings have reported formation of mineralized tissue from ~7th to 10th day upon contact with Ca(OH) 2 , with complete bridge formation in 4 weeks sealing pulp exposure [ 68 , 69 ]. In the present study, in vitro CHX-release profiles show ~94.94% of CHX released in ~15 days ( Figure 9 a) and it is anticipated that the CHX-loaded/Ca(OH) 2 microparticles continue to release CHX in a sustained manner beyond this specified time-period.…”
Section: Discussionmentioning
confidence: 99%